INTERNALISASI NILAI DEMOKRASI PANCASILA MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH - Rijal, Moch. Syaiful; Bakhtiar, M. Arif; laili, Innayatul; Damayanti, Ayu Maya (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This article aims to analyze the process of internalizing the values of Pancasila Democracy through Pancasila Education learning in schools as an effort to develop students’ democratic character. Pancasila Education plays a strategic role in instilling democratic values, particularly those embodied in the fourth principle of Pancasila, so that they are not only understood conceptually but also implemented in students’ attitudes and behavior in everyday life. This study employs a qualitative approach using a literature review method, with data sources consisting of scholarly journal articles, academic books, and relevant educational policy documents. The data were analyzed using content analysis techniques to examine concepts, strategies, and practices related to the internalization of Pancasila Democratic values in learning. The results indicate that the internalization of democratic values is carried out through the integration of democratic principles into the curriculum, the application of participatory learning methods such as Problem-Based Learning, Project-Based Learning, simulations, and deliberative discussions, as well as the strengthening of a democratic school culture. The discussion emphasizes that the role of teachers as facilitators and democratic role models, the support of the Merdeka Curriculum, and adaptation to the challenges of the digital era are key factors in the successful internalization of these values.